Immune modulation by nutritional intervention in malnourished children: Identifying the phenotypic distribution and functional responses of peripheral blood mononuclear cells - Noor, Zannatun; Hasan, Md. Mehedi; Gazi, Md. Amran; Hossaini, Farzana; Haque, Nur Muhammad Shahedul; Palit, Parag; Fahim, Shah Mohammad; Das, Subhasish; Mahfuz, Mustafa; Marie, Chelsea; Petri, William A.; Haque, Rashidul; et al. (Scandinavian journal of immunology, 2023)
Malnourished children are susceptible to an increased risk of mortality owing to impaired immune functions. However, the underlying mechanism of altered immune functions and its interaction with malnutrition is poorly understood. This study investigates the immune function and evaluates the effect of a particular nutritional intervention on the immune cells of undernourished children. Stunted (LAZ <−2) and at‐risk of being stunted (length‐for‐age Z‐scores, LAZ <−1 to −2) children aged between 12 and 18 months were enrolled and were provided with the daily nutritional intervention of one egg and 150 mL cow's milk for 90 days. Peripheral blood mononuclear cells (PBMCs) were isolated at enrolment and upon completion of the intervention. Phenotypic profiles for CD3+ cells, CD4+ cells, CD8+ cells, NKT cells, and B cells were similar in both cohorts, both before and after the intervention. However, activated B cells (CD25+) were increased after nutritional intervention in the at‐risk of being stunted cohort. Several pro‐inflammatory cytokines, IL‐6, IFN‐γ, and TNF‐α, were elevated in the stunted children following the nutritional intervention. The results of the study indicate that nutritional intervention may have a role on activated B cells (CD25+) s in children who are at‐risk of being stunted and may alter the capacity of PBMC to produce inflammatory cytokines in stunted children.